Synthesis of novel purine derivatives: Antiplatelet aggregation activity evaluation and 3D‐QSAR analysis. (12th August 2022) - Li, Shunlai; Ren, Yajing; He, Qiwen; Wei, Yongji; Du, Hongguang
Abstract: Cardiovascular disease caused by platelet aggregation is a serious threat to human health, so antiplatelet aggregation has great significance to treat the disease. Since, purine derivatives are important molecules with antiplatelet aggregation activity, it is very essential to study the relationship between purine structure and antiplatelet aggregation effect, which could help us to find antithrombotic drugs. This article describes the modification of molecular substituents with purine structures as backbone and evaluates their antiplatelet aggregation activity. 3D‐QSAR analysis of a series of novel purine derivatives synthesized was performed based on self‐organized molecular field analysis (SOMFA). Significant correlation coefficients (SOMFA, r 2 = 0.821, rcv 2 = 0.807, F value = 283.500, SEE = 0.229) were obtained, and the model prediction ability was validated using the test set. The results suggest that rational modification of the substituent groups can provide a basis for the development of more effective drug molecules. Abstract : In this paper, a series of novel purine derivatives were synthesized, their antiplatelet aggregation activities were measured, and SOMFA model was established for 3D‐QSAR analysis.